(untitled) (Research, Society and Development, 2024)
Adolescence is a crucial period for human development, with impacts on the most diverse aspects. During this period, while there is a vulnerability to the development of psychological problems, it is also the ideal time to implement promotional and preventive actions in mental health. Referenced by Paulo Freire’s Pedagogy, occupational therapists can play an important role in promoting the mental health of adolescents. This article aims to reflect on an Occupational Therapy intervention process aimed at promoting mental health with adolescents supported by Paulo Freire’s theoretical-methodological framework. Documentary research carried out in the database of a research and extension project that developed interventions with teenagers in the 8th year of elementary school at a Municipal School in the City of Recife, carried out in 7 steps and with data analyzed using the Content Analysis technique . The results present aspects of the construction of actions and reflections on the experience of Freirean principles, referring to the materialization of the foundations of dialogue, in addition to the discussion of the impacts of the experience on training in Occupational Therapy. It was concluded that working to promote mental health with and for adolescents is a challenge to be understood from the perspective of hope and that developing educational actions based on dialogue mean more than giving space to an active and participatory methodology, it also means believing that everyone involved in the interventions can transform their reality and be transformed by it as beings of praxis who seek to be ser mais.